2013
DOI: 10.3171/2013.8.jns13224
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acromegaly by endoscopic transsphenoidal surgery: surgical experience in 214 cases and cure rates according to current consensus criteria

Abstract: Object Acromegaly is a disease that has significant morbidity and mortality related to high levels of growth hormone (GH) and insulin-like growth factor–I (IGF-I), and is usually caused by pituitary adenomas. The goal in this study was to investigate the role of endoscopic transsphenoidal surgery and surgical experience in the treatment of GH adenoma cases in relation to surgical results and hormonal cure rates, and to perform a review of the literature. Methods The authors present a retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 46 publications
5
53
1
2
Order By: Relevance
“…Tumor size predicted remission, and microadenomas had higher hormonal remission rates than macroadenomas in our series reported in numerous earlier publications (15,17,29). In our current study, remission was achieved in 80% of microadenomas and in 64.7% of macroadenomas.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Tumor size predicted remission, and microadenomas had higher hormonal remission rates than macroadenomas in our series reported in numerous earlier publications (15,17,29). In our current study, remission was achieved in 80% of microadenomas and in 64.7% of macroadenomas.…”
Section: Discussionsupporting
confidence: 62%
“…The 2010 criteria are more stringent than 2000 criteria and it is more difficult to achieve a hormonal remission according to the new criteria. There are limited numbers of studies in literature according to the new criteria, and hormonal remission rates were reported between 46%-70% (12, 15,16,29). In our series, hormonal remission was achieved in 66.1% of patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…2017; 4(3):e14131. 5 ies using the 2010 criteria with the reported remission rates of 28.8% to 70.8% (7,19,(26)(27)(28)(29)(30)(31)(32)(33). The current study results showed an overall remission rate of 71.4% with the mean follow-up of 25.4 months.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast to earlier publications, tumor size was not an important predictive factor for remission in the current study (19,32,33). Sarkar et al, revealed that an adenoma size < 20 mm was the predictor of outcome at follow-up (27).…”
Section: Discussioncontrasting
confidence: 55%